Artificial nerve conduit for guiding peripheral nerve growth (cadaveric study) - A. G. Fedyakov; E. A. Nemets; O. N. Dreval; A. V. Gorozhanin; L. A. Sidneva; Z. H. Plieva; M. A. Razin; N. V. Perova; V. I. Sevastianov (Вестник трансплантологии и искусственных органов)
At present, the search for effective ways of restoring peripheral nerves with anatomical damage continues. Autoplasty still remains the gold standard, which, however, is not without its drawbacks. The use of nerve implants for promoting directional axon growth is essential and promising.Objective: to study the biomechanical properties of laboratory samples of an artificial nerve conduit (NGC) made of hybrid biomaterials and to, on cadaveric material, assess the technical feasibility of using them in surgical practice to repair extended peripheral nerve defects.Material and methods. The objects of the study were three electrospun NGC samples: from synthetic material (polycaprolactone, PCL) and hybrid biomaterials (PCL + gelatin or PCL + collagen). The work compared the physical and mechanical properties of NGC: stiffness, plasticity, elasticity, brittleness, resistance to chemical attack, their ability to be impregnated with liquid media, permeability, possibility of making an anastomosis between the implant and the nerve during surgical procedure. Cadaveric material was the object of the study: we used a dissected superficial sensory branch of the human right radial nerve, 2 mm in diameter, isolated on the forearm, about 12 cm in length, because it most corresponded to the diameter of the NGC samples tested. After surgery, the echogenic features of the implants and their anastomoses with the nerve were assessed by ultrasound imaging.Results. It was found that hybrid NGC samples, based on their biomechanical properties, are fundamentally suitable for use in surgical practice, to ensure growth and replacement of a peripheral nerve defect. However, the best composition of a nerve guide can be established after comparative preclinical study of the biocompatible and functional properties of hybrid material samples.Conclusion. The physical and mechanical properties of the investigated NGC samples made of hybrid biomaterials meet the technical requirements for implantable nerve conduits for surgical application.